Tetra- and octa-[4-( thiophen-3-yl)phenoxy]-bearing metal-free and Lu(III) phthalocyanines: synthesis, characterisation and investigation of photophysical properties - Ozdemir, Merve; Kilicarslan, Fatma Aytan; Erdogmus, Ali; Erden, Ibrahim (SCIENCE REVIEWS 2000 LTD, 2016)
4-[4-(Thiophen-3-yl)phenoxy] phthalonitrile and 4,5-bis[4-(thiophen-3-yl) phenoxy] phthalonitrile and their corresponding tetra-and octa-substituted metal-free and Lu(III) phthalocyanine derivatives have been synthesised. The aggregation behaviour of the phthalocyanine compounds has been investigated in different solvents and concentrations and the effects of the substituent and the lutetium on their photophysical properties are reported.
Keywords: phthalocyanine; fluorescence; aggregation; lutetium(III); LUTETIUM(III) PHTHALOCYANINE; PHOTOCHEMICAL PROPERTIES; MAGNETIC-PROPERTIES; Chemistry